2021
DOI: 10.3390/su13168754
|View full text |Cite
|
Sign up to set email alerts
|

To Rebuild or Relocate? Long-Term Mobility Decisions of Hazard Mitigation Grant Program (HMGP) Recipients

Abstract: Limited funds and the demand for disaster assistance call for a broader understanding of how homeowners decide to either rebuild or relocate from their disaster-affected homes. This study examines the long-term mobility decisions of homeowners in Lumberton, North Carolina, USA, who received federal assistance from the Hazard Mitigation Grant Program (HMGP) for property acquisition, elevation, or reconstruction following Hurricane Matthew in 2016. The authors situate homeowners’ decisions to rebuild or relocate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Our research also advises that policymakers and practitioners devote resources and capacity building toward addressing inequality in these areas. Given that the allocation of financial resources for hazard reduction often favors particular communities (Seong et al, 2021(Seong et al, , 2022, our findings will support equitable heat mitigation initiatives.…”
Section: Discussionmentioning
confidence: 71%
“…Our research also advises that policymakers and practitioners devote resources and capacity building toward addressing inequality in these areas. Given that the allocation of financial resources for hazard reduction often favors particular communities (Seong et al, 2021(Seong et al, , 2022, our findings will support equitable heat mitigation initiatives.…”
Section: Discussionmentioning
confidence: 71%
“…Given that, urban planners can envision highlighting the need to address the digital divide by designing a more advanced application layer with decision-specific algorithms for equitable outcomes. Building upon the findings of Seong, Losey, and Van Zandt (2021), and Seong, Losey, and Gu (2022), which reveal that resource allocation for hazard mitigation often disproportionately benefits specific communities due to unequal resource distribution in decision-making processes, disaster planners must adopt and incorporate smart city technologies to address efficiency, sustainability, and equity concerns in urban resilience. The smart disaster resilience framework must consider the social and economic ramifications of disasters, which disproportionately impact disadvantaged groups when viewed through the “lens of social vulnerability” (French, Feser, and Peacock 2008; Peacock et al 2014).…”
Section: Discussion For Future Researchmentioning
confidence: 99%
“…Climate change will continue to exacerbate conditions that increase the risk of illness and injury. Following hurricanes Katrina and Harvey, physical and mental health-related problems were welldocumented, particularly for children, the elderly, and lower income households (Ashley and Ashley, 2008;Qiang, 2019a;Seong et al, 2021;Mazumder et al, 2022). A community survey of respondents in Austin, Texas found that social vulnerability has a large, negative and statistically significant effect on risk perception (Bixler et al, 2021).…”
Section: Social Vulnerabilitymentioning
confidence: 99%